2018
DOI: 10.1007/s13311-018-0634-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Pimozide Fails to Attenuate Motor and Pathological Deficits in Two Mouse Models of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease which presently does not have any efficient therapeutic approach. Pimozide, a Food and Drug Administration (FDA)-approved neuroepileptic drug, has been recently proposed as a promising treatment for ALS patients based on apparent stabilization of right hand muscles after a short-time administration. A new clinical trial started at the end of 2017 to recruit patients with a prolonged drug delivery schedule. Here, our aim was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A drug-screening platform in C. elegans and zebrafish models of ALS identified pimozide, an already approved neuroleptic, as a NMJ stabilizer by blocking T-type Ca 2+ channels (Patten et al, 2017). Despite some benefits in neurophysiologic measures were reported in hSOD-1 G93A mice and human patients in the first report, one study assessing long-term effects showed warned caution, as worsening of survival and muscle function were observed in mutant SOD1, and TDP-43 mice models (Pozzi et al, 2018). Notably, an agonist antibody directed toward muscle-specific kinase (MuSK), a post-synaptic tyrosine kinase receptor essential for NMJ maintenance, preserved motor synapses, delayed muscle denervation and extended lifespan in hSOD-1 G93A ALS mice (Cantor et al, 2018).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…A drug-screening platform in C. elegans and zebrafish models of ALS identified pimozide, an already approved neuroleptic, as a NMJ stabilizer by blocking T-type Ca 2+ channels (Patten et al, 2017). Despite some benefits in neurophysiologic measures were reported in hSOD-1 G93A mice and human patients in the first report, one study assessing long-term effects showed warned caution, as worsening of survival and muscle function were observed in mutant SOD1, and TDP-43 mice models (Pozzi et al, 2018). Notably, an agonist antibody directed toward muscle-specific kinase (MuSK), a post-synaptic tyrosine kinase receptor essential for NMJ maintenance, preserved motor synapses, delayed muscle denervation and extended lifespan in hSOD-1 G93A ALS mice (Cantor et al, 2018).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…It has also enhancing effects on the neuromuscular transmission in ALS (Patten et al, 2017). Although not effective in two mouse models of ALS (Pozzi et al, 2018), pimozide is investigated in ALS in a placebo-controlled phase 2 trial (NCT03272503).…”
Section: Other Clinical Trials Employing Drugs Acting On Different Mechanismsmentioning
confidence: 99%
“…Unexpectedly, pimozide aggravated pathology in both models. Significant increase of pathogenic protein aggregate accumulation in the nervous system, worsening of the neuromuscular connectivity and consecutively, motor functions and reduced lifespan were observed for pimozide‐treated compared with vehicle‐treated animals 38 . Reasons for a damaging effect of chronic pimozide treatment on mouse models of ALS pathology are not clear but these latest observations cast doubts on the future of this drug for ALS treatment.…”
Section: Drugs Used For Treatment Of Psychiatric Disordersmentioning
confidence: 99%